Otimização das condições de cultivo de Erysipelothrix rhusiopathiae para produção de vacina contra erisipela suína - Silva, Adilson José da (Universidade Federal de São Carlos, 2016)
Made available in DSpace on 2016-08-17T18:39:28Z (GMT). No. of bitstreams: 0 Previous issue date: 2007-03-30 === Valée S.A. === Swine erysipelas is one of the diseases responsible for the great economic losses in swine-producing areas of the world. The bacteria Erysipelothrix rhusiopathiae is the causative agent of erysipelas, and the vaccines currently available for prevention of this disease are produced with the whole broth culture containing the inactivated microorganism or its live-attenuated form. A surface protein was identified as the main antigen. It can be found in the culture supernatant or attached to the cell wall through interactions with the choline residues from the teichoic and lipoteichoic acids of this structure. Considering the lack of information in the scientific literature about studies concerning the growth pattern of this pathogen, the company Vallèe S.A, a Brazilian industry of veterinary pharmaceutical products, established a partnership with researchers form the Chemical Engineering Department of UFSCar with the purpose of developing the technology required for the production of the cited vaccine. In this context, the objective of this work was to optimize the growing conditions of E. rhusiopathiae to establish a protocol for production of high cellular concentrations, enough to prepare a vaccine against swine erysipelas offering the same or a higher protection level compared to the commercially available formulations. To achieve this goal, the growth kinetics of this microorganism was investigated under different aeration conditions (aerobiosis, anaerobiosis and microaerophilic condition), changes in the medium nutrient s concentration were analyzed, and mice protection tests using the prepared vaccines were performed. The studies about the aeration influence on the microorganism growth and the antigen expression were made using a 4.0 L stirred-tank bioreactor, with an agitation frequency kept between 100 and 400 rpm and air or N2 flow rate of 1.0 L/min. The studies for the improvement of the medium formulation were carried out in flasks incubated at static condition or under agitation of 200 rpm. The vaccines were prepared using medium harvested in both conditions. The temperature was set at 37°C and the initial pH at 8,0 in all experiments. Samples of culture supernatant and from cell extracts made with choline chloride were analyzed by electrophoresis under denaturating conditions (SDS-PAGE) to evaluate the antigen expression. The preliminary electrophoresis results indicated that the antigen production is associated to the cell growth and its expression is favored in the presence of oxygen. Cellular concentrations around 1,8 g/L were reached, in all different aeration conditions employed, using the stirred-tank bioreactor operating with pH automatic control and using the culture medium with nutrients concentrations increased in 50 % from the Feist medium described in literature. The vaccines prepared in aerobic and microaerophilic condition led to higher protection levels in the challenge-exposure tests, and a formulation made from an aerobic culture in bioreactor having a cellular concentration over 2,0 x 109 CFU/mL showed the same immunizing power as the three commercial vaccines used for comparison purposes. Observations about the inhibitory effects of metabolites accumulation and substrate saturation on the microorganism growth pointed the fed-batch as a promising operation mode to produce larger amounts of biomass. Cellular concentrations reached in the experiment ran under these condition were increased around five times. === A erisipela suína está entre as enfermidades que causam os maiores prejuízos na suinocultura mundial. O agente patogênico associado a esta doença é a bactéria Erysipelothrix rhusiopathiae, e as vacinas disponíveis atualmente para a prevenção da erisipela são produzidas com o caldo de cultivo deste microrganismo inativado ou atenuado. O principal antígeno identificado é uma proteína de superfície da bactéria encontrada no sobrenadante do caldo de cultivo ou aderida à parede celular através de interações com resíduos de colina dos ácidos teicóico e lipoteicóico desta estrutura. Diante da escassez de informações na literatura científica sobre estudos a respeito do crescimento deste patógeno, a empresa Vallèe S.A, indústria brasileira de produtos farmacêuticos de uso veterinário, firmou uma parceria com pesquisadores do Departamento de Engenharia Química da UFSCar para o desenvolvimento da tecnologia de produção dessa vacina. Assim, o presente trabalho teve como objetivo otimizar as condições de cultivo de E. rhusiopathiae de forma a estabelecer um protocolo de produção de altas concentrações celulares deste microrganismo, suficientes para produzir uma vacina contra a erisipela suína que oferecesse grau de proteção igual ou superior às formulações disponíveis no mercado. Para tanto, o crescimento do microrganismo foi estudado em diferentes condições de aeração (aerobiose, microaerofilia e anaerobiose), foram avaliadas alterações nas concentrações dos nutrientes do meio de cultivo e foram realizados testes de imunização em camundongos com as vacinas preparadas. Os estudos sobre o efeito da aeração no crescimento do microrganismo e na expressão do antígeno foram realizados em biorreator de 4,0 L, com uma faixa de agitação entre 100 e 400 rpm e vazão de ar ou N2 de 1,0 L/min. Os experimentos de aprimoramento do meio de cultivo foram conduzidos em câmara incubadora estática ou com agitação de 200 rpm. Já as vacinas foram preparadas em ambas as condições. A temperatura utilizada foi de 37°C e o pH inicial foi de 8,0 em todos os ensaios realizados. A expressão do antígeno foi avaliada por eletroforese em condições desnaturantes (SDS-PAGE) utilizando amostras do sobrenadante dos cultivos ou a partir de extratos das células preparados com solução de cloreto de colina. Os resultados destas análises revelaram que a produção do antígeno acompanha o crescimento celular e sua expressão é favorecida na presença de oxigênio. Concentrações celulares de até 1,8 g/L foram atingidas, nas três diferentes condições de aeração empregadas, nos cultivos realizados em biorreator com controle automático de pH e utilizando o meio de cultivo com as concentrações de nutrientes aumentadas em 50% em relação ao meio Feist modificado descrito na literatura. As vacinas preparadas com os cultivos aeróbio e microaerófilo proporcionaram um maior grau de proteção nos testes de imunização realizados, e a formulação preparada a partir de um cultivo aeróbio realizado em biorreator com concentração celular superior a 2,0 x 109 UFC/mL conferiu o mesmo nível de proteção que três vacinas comerciais utilizadas para fins de comparação. Observações sobre os efeitos de inibição do crescimento provocadas por acúmulo de metabólitos ou excesso de substrato, indicaram o modo de operação do biorreator em batelada alimentada como promissor para obtenção de maior concentração celular. Em um experimento realizado nesta condição a biomassa foi aproximadamente quintuplicada em relação aos ensaios em batelada simples.